The Possibilities of Multislice computed Tomography in nasal Anthropometry - D. A. Lezhnev (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Background. Nasal anthropometry is an important aspect of maxillofacial and plastic surgery especially in the preoperative stage of rhinoplasty. Multislice computed tomography (MSCT) permits to assess quantitative the variant nasal anatomy using measuring.Aims: to determine the possibilities of MSCT-anthropometry in nasal configuration grade.Materials and methods. We performed a proand retrospective analysis of MSCT data of maxillofacial region of 50 patients (aged 35 ± 10.7 years old) with changes of nasal height and width and 35 women (32.9 ± 8.4 years old) with normal nasal configuration. The variant anatomy consists in long nose (n = 16), short nose (n = 17), wide nose (n = 17). The nasal height was measured from the nasal root (nasion) to the nasal base (subnasion), the nasal width is the distance between the most lateral aspects of the alae nasi. Besides, the nasal index was calculated. The descriptive statistics of obtained data were presented by mean and standard deviation (SD), also the multiple regression analysis was used. Values of p = 0.005 were considered statistically significant.Results. The results showed that the average nasal height in patients with normal configuration is 51.9 ± 2.63 mm, with short nose – 45.2 ± 1.36 mm, with long nose – 60.3 ± 1.28 mm. The mean nasal widths are 34.9 ± 1.88 mm in normal configuration, 38.8±3.57 in wide nose. The nasal indexes were calculated, their features were detected. These obtained results correlate with anthropometric data of different studies.Conclusions. MSCT-anthropometry is an objective imaging method of variant nasal anatomy that could provide improving quality of diagnostics of patients seeking rhinoplasty and choose a surgical approach.